Responsibility of Foundation Organs As a Result of Unlawful Acts in The Organization of Higher Education Foundations - Zulkarnain, A. (Journal of Law, Politic and Humanities, 2024)
This research focuses on the Responsibilities of Foundation Organs as a Result of Unlawful Actions in the Implementation of Higher Education Foundations. The research method used is Normative Juridical with a statutory, theory/concept, case approach, which is related to the implementation of higher education foundations. Then the data used is secondary data in the form of primary and secondary legal materials. The results of this research show that a form of unlawful action by foundation organs related to the management of Higher Education Foundations is accepting the distribution or transfer of foundation assets as intended in Article 70 paragraphs (1) and (2) UUY No. 16 of 2001 which has been amended by Law. No. 28 of 2004, embezzling money from foundation assets as regulated in Article 372 of the Criminal Code, making agreements with organizations or other parties affiliated with the founder or other foundation organs without the approval of the Trustees the foundation, deviated from its duties and authority as a foundation organ, as regulated in the UUY and in the foundation's AD/ART. Actions against the law by foundation organs harm the foundation and related third parties. As for The responsibilities of Foundation Organs related to unlawful acts in the management of the foundation are criminal responsibility in the form of imprisonment and/or/ fines, and civil responsibility in the form of compensation both individually and jointly, as well as administrative responsibility in the form of reprimand sanctions up to dismissal from position as a foundation organ. It is recommended not to establish a higher education foundation if the founder or foundation organ wants to seek personal or group profit because it conflicts with the aims and objectives of the foundation. Suitable means for seeking personal or group profits are through Limited Liability Companies (PT), Firms, Trading Businesses (UD) and the like.